2020
DOI: 10.1109/access.2020.2999673
|View full text |Cite
|
Sign up to set email alerts
|

Deep2s: Improving Aspect Extraction in Opinion Mining With Deep Semantic Representation

Abstract: Syntactical rule based approaches for aspect extraction, which are free from expensive manual annotation, are promising in practice. These approaches extract aspects mainly through the dependency relations in the surface sentence structures. However, deep and rich semantic information hidden in sentences which can help improve aspect extraction, is difficult for them to capture. In order to address the problem, this paper first proposes to employ Logic Programming to explore the feasibility of deep semantic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…As illustrated in Figure 2, aspect extraction solutions can be classified as either being rule-based, unsupervised, or supervised. [17]. Zainuddin et al (2017) [13] employed a Stanford dependency parser to extract aspects from texts by breaking them down into distinct grammatical components and determining the implicit aspect words or phrases based on the grammatical dependencies extracted.…”
Section: -Background Studymentioning
confidence: 99%
See 1 more Smart Citation
“…As illustrated in Figure 2, aspect extraction solutions can be classified as either being rule-based, unsupervised, or supervised. [17]. Zainuddin et al (2017) [13] employed a Stanford dependency parser to extract aspects from texts by breaking them down into distinct grammatical components and determining the implicit aspect words or phrases based on the grammatical dependencies extracted.…”
Section: -Background Studymentioning
confidence: 99%
“…Lastly, the rule-based aspect extraction solution proposed by Li et al (2020) [17] adopted a framework based on the Answer Set Programming (ASP) [19] logic programming paradigm. Their solution first modeled the relationships between the words in its input texts using Abstract Meaning Representation (AMR) graphs [20].…”
Section: -Background Studymentioning
confidence: 99%
“…Effective analysis of public opinion about products and services through AI has become the basis of marketing strategies today. Researchers, using a scientometric approach, thematic and patent search methods, and extended citation, collect a lot of bibliographic records of opinion mining research, in-depth semantic analysis identify intellectual landscapes and recent events, record citation trends at the level of each domain, assignment of thematic categories, keyword matching, a network of joint citation of documents, and essential articles (Li et al, 2020;Jang et al, 2022). The study of algorithmic and linguistic aspects of collecting opinions is of the most significant interest to the Internet community in terms of understanding, quantifying and applying the emotional orientation of texts.…”
Section: Sarcasm and Hidden Emotions Detectionmentioning
confidence: 99%
“…The study of algorithmic and linguistic aspects of collecting opinions is of the most significant interest to the Internet community in terms of understanding, quantifying and applying the emotional orientation of texts. Based on the analysis of recent thematic trends, the authors concluded that the practical application of intelligent opinion analysis: forecasting market value and analyzing product reviews attracts the most significant attention of the community (Tsapatsoulis and Djouvas, 2019;Li et al, 2020;Jang et al, 2022).…”
Section: Sarcasm and Hidden Emotions Detectionmentioning
confidence: 99%
See 1 more Smart Citation